Chaucerian Theatricality. - Ganim, John M. (Princeton legacy library., 2014)
Whereas modern criticism has emphasized the unity and sense of permanence in The Canterbury Tales, John Ganim alerts us to a dialectically opposing dimension that Chaucer's poetics shares with the popular culture of the late Middle Ages: his celebration of the ephemeral and his sense of performance. Ganim uses the concept of theatricality to illuminate Chaucer's manipulations of the forms of popular culture and high literary discourse. He calls upon recent work in semiotics and social history to question Mikhail Bakhtin's notion of the ""carnivalesque"" and the ""dialogic, "" at the same tim.